Green cities? Urbanization, trade and the environment - Rainald Borck; Michael Pflüger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study environmental pollution in an economic geography framework with two cities, where pollution arises from commuting within cities, goods transport between cities, production of manufacturing and agricultural goods, and residential energy use. We find that city size has an ambiguous effect on pollution levels. We also analyse how pollution changes with varying trade freeness, skilled wage income, and commuting costs.
Keywords: Q54; R12; F12; 330